Production of cellulase and ethanol using pretreated sugarcane bagasse via an in situ saccharification and fermentation system / Yoon Li Wan - Yoon, Li Wan (2015)
Agricultural waste generated in substantial amount has led to massive disposal problem. One of the solutions to tackle this issue is converting the low cost lignocellulosic waste into value-added products such as enzymes and ethanol. In this study, the production of multiple value-added products from sugarcane bagasse (SCB) was examined by adopting an in situ saccharification and fermentation system in a single reactor with white-rot fungus (WRF) and yeast. To achieve the objective, the aspects on chemical pretreatment of SCB, solid state fermentation (SSF) for cellulase and reducing sugar (RS) production using WRF and the ethanol production via sequential-co-culture of WRF and yeast were investigated. The performance of ionic liquid (IL) on pretreating SCB was compared with the conventional acid and alkali pretreatment based on RS production and structural modification of SCB. Sodium hydroxide (NaOH) and IL 1-ethyl-3-methylimidazolium acetate ([EMIM][Ac]) pretreatment mediums have better performance in terms of exerting higher RS yield and greater structural modifications to SCB compared to sulphuric acid (H2SO4), 1-butyl-3-methylimidazolium chloride ([BMIM][Cl]) and 1-ethyl-3-methylimidazolium diethyl phosphate ([EMIM][DEP]). Between the two potential pretreatment mediums, NaOH was selected due to its higher RS yield of 97.8%, ability in producing SCB with a more porous and delignified structure and lower reagent cost. Through screening on four types of WRF for their suitability in co-culture with yeast Saccharomyces cerevisiae, Pycnoporus sanguineus fulfilled the selection criteria by giving a relatively high amount of RS with 2 g /100 g SCB and producing cellulase with a maximum of 0.02 IU/mL FPase, 0.11 IU/mL CMCase and 0.13 IU/mL β-glucosidase, besides being compatible with S. cerevisiae. The suitability of NaOH-pretreated SCB for SSF was confirmed when the structure and composition of NaOH-pretreated SCB induced a higher production of RS in situ which was favorable for subsequent ethanol production. The highest amount of RS of 3.1 g/100 g SCB was obtained from SSF when 0.6% inoculum loading, 70% moisture content and 4 days was applied. The highest RS yield was insufficient for ethanol production. Thus, a saccharification step at 50ºC was incorporated after SSF to enhance the RS production to 9.4 g/100g SCB before S. cerevisiae was sequentially inoculated. To facilitate better ethanol production, non-agitated submerged condition with liquid to solid ratio of 25 mL to 1 g SCB and 30 g/L yeast inoculum was adopted. The in situ solid state fermentation, saccharification and submerged fermentation system by sequential-co-culturing P. sanguineus and S. cerevisiae produced a maximum of 4.5 g ethanol/100 g SCB. Furthermore, the experimental data of kinetic study on ethanol production was well fitted into the modified Gompertz model. Ethanol production via co-culture of P. sanguineus and S. cerevisiae that are both existed in natural habitat and widely available has never been reported. Besides ethanol production, simultaneous production of cellulase and RS from pretreated SCB through co-culture of these strains was proven feasible. The consolidated bioprocess of this work coupled with preliminary kinetic study would provide good reference to the large scale production of multiple value-added products from SCB with minimized unit operations.